Kansas Field Research 2018 (Kansas Agricultural Experiment Station Research Reports, 2018)
The research program at the Kansas State University East Central Kansas Experiment Field is designed to keep area crop producers abreast of technological advances in agronomic agriculture. The Kansas State University Kansas River Valley Experiment Field was established to study management and effective use of irrigation resources for crop production in the Kansas River Valley (KRV).
Keywords: Experiment fields